Agatha Christie partners in crime. The Tommy & Tuppence mysteries [videorecording (DVD)] - Annis, Francesca, 1945-; Warwick, James, 1947-; Christie, Agatha, 1890-1976 (Acorn Media, 2013)
From the mind of mystery maven Agatha Christie comes what is considered to be the original crime-solving couple, Tommy and Tuppence Beresford. Redefining the conventions of the mystery genre, providing a prototype for many male/female detective teams that followed.